2021
DOI: 10.3390/ijerph18062811
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Gambling, Buying and Materialism in Adolescents: A Population-Based Study

Abstract: Gambling disorder, gambling-related cognitive biases, compulsive buying, and materialistic values lead to impaired functioning in important areas of life. The aims of the present longitudinal study are (1) to evaluate the change produced after one year in those mentioned variables and (2) to examine the gender role in these changes and to analyze the mediational mechanisms among the variables of the study. The sample was composed of 182 adolescents (103 females and 79 males) from secondary education Spanish in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 72 publications
0
10
1
Order By: Relevance
“…Concerning addictive behaviours, compulsive spending stands out as the addiction that correlates the highest with emotional dependence. In this study, sex differences were found in this type of addiction, as males showed higher scores that females in compulsive spending, an information that contradicts data from other studies, showing a greater presence of compulsive spending in females than in males ( Estévez et al, 2021 ). However, it is noteworthy that, in this study, the males obtained higher scores in emotional dependence.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Concerning addictive behaviours, compulsive spending stands out as the addiction that correlates the highest with emotional dependence. In this study, sex differences were found in this type of addiction, as males showed higher scores that females in compulsive spending, an information that contradicts data from other studies, showing a greater presence of compulsive spending in females than in males ( Estévez et al, 2021 ). However, it is noteworthy that, in this study, the males obtained higher scores in emotional dependence.…”
Section: Discussioncontrasting
confidence: 99%
“…However, previous studies point to sex differences depending on the type of addiction. For example, being male is associated with greater severity of pathological gambling disorder, or, on the contrary, compulsive spending is higher in females ( Estévez et al, 2021 ). People who are exposed to violent situations may develop higher emotional dependence patterns, which could also contribute to the repetition of suffering or receiving violence patterns in certain situations.…”
Section: Discussionmentioning
confidence: 99%
“…Although the research just reviewed suggests that the negative effects of materialism may not be that severe in terms of general life satisfaction, we want to be clear that we are not suggesting the negative effects of materialism are trivial. In particular, the Dittmar et al (2014) meta‐analysis showed very strong relations between materialism and compulsive/impulsive 2 consumption and moderate relations with risk behaviors (see Estévez et al, 2021, for evidence of the bidirectional relation between materialism and compulsive consumption). Higher levels of materialism are also associated with poor money management (Donnelly et al, 2012; Zhang et al, 2016), higher levels of debt (Richins, 2011; Watson, 2003), and pathological gambling (Netermeyer et al, 1998).…”
Section: Consequences Of Materialismmentioning
confidence: 99%
“…The prevalence of BSD has been estimated within a large range between 1% to 8% in industrialized countries (this wide interval is related to the large heterogeneity of the study samples and the measurement tools), with a mean point estimate of 5% according to a meta-analysis [20]. Furthermore, both clinical and population-based studies have reported an increasing trend for BSD in developing consumer societies [21], highlighting the central relevance of materialistic values among these cultures as a predisposing factor to compulsive buying attitudes [22,23]. Epidemiological research has also reported an increasing propensity toward BSD among young adults and women, suggesting a greater tolerance for women and younger age individuals to make excess purchases [24].…”
Section: Introductionmentioning
confidence: 99%